SOSIALISASI PENYUSUNAN LAPORAN LABA RUGI SEDERHANA BAGI KELOMPOK USAHA MIKRO KECIL DAN MENENGAH PADA UMKM GADING BERSINAR - Soeparyono, Regina Deia; Khuluqi, Khusnul; Sugeng, Andry (Publika Citra Media, 2024)
The profit and loss report is part of a company's financial report produced in an accounting period which describes the elements of the company's income and expenses to produce a net profit (or loss). MSMEs are independent productive economic enterprises, usually carried out by individuals or business entities that are not subsidiaries or branches of companies owned, controlled or part of directly or indirectly. Business actors in the Gading Shining UMKM are part of the UMKM. The problem faced by MSME actors is related to the inability of MSME actors to prepare profit and loss reports for their businesses. MSME players claim that they do not have knowledge regarding making profit and loss reports. This Community Service activity aims to prepare a simple profit and loss report for Gading Bersinar MSME players so that it can be used to manage and build MSMEs and collaborate with bankers, investors and other business partners. The method developed in this activity involves socializing the preparation of simple profit and loss reports for Gading Bersinar MSMEs. So with this activity regarding the socialization of simple profit and loss reports, it is intended to provide understanding in making simple profit and loss reports for ivory shining MSME players so that they can be directly applied in their businesses.